Customer satisfaction in the legal service industry in Malaysia / Rabiha Ibrahim - Ibrahim, Rabiha (1997)
The literatures on product and service marketing have discussed and submitted that product and services can either be seen as two different things or as an entity. Under the first notion, the marketing researchers argue that products are manufactured output while services involve people. Products are tangible things, thus during the selling or purchase process the sellers are able to deliver the products direct to the consumers. Meanwhile, during the purchase process of services, the sellers or service providers have to focus upon the pre-sale and after -sale activities offered to the consumer. Under the second notion, the researchers view product/service as an entity. As stated by Levitt (1981), "Everybody is in service". As such, all consumers purchase entities. The differences lie in the greater component of services involves in an entity.